Florence Foster Jenkins [videorecording (DVD)] - Streep, Meryl; Grant, Hugh; Helberg, Simon (Paramount, 2016)
A New York socialite who dreams of becoming a great opera singer. While the voice she hears in her head is beautiful, to everyone else it is hilariously awful. Her husband and biggest fan, St. Clair Bayfield is determined to protect his beloved Florence from the truth. But when Florence stages a huge concert at Carnegie Hall, he faces his greatest challenge to make sure her performance is a rousing success.